FORMULASI DAN UJI STABILITAS FISIK NANOSTRUCTURE LIPID CARRIER KOENZIM Q10 DARI CAMPURAN FRAKSI SETIL PALMITAT - Silvi Ayu Wulansari; Lailatus Sadiyah (As-Syifaa Jurnal Farmasi, 2026)
Coenzyme Q10 (CoQ10) is an additional supplement that acts as an antioxidant agent and plays an anti-aging role in the skin. One of the factors that can support the penetration of coenzyme Q10 into the skin is the use of the Nanostructured Lipid Carrier (NLC) system. Differences in the concentration of solid lipids used in the NLC system can play an important role in controlling drug release, so that topical use of Coenzyme Q10 can work optimally. The aim of this study is to determine the effect of solid lipid concentration on the stability of Nanostructured Lipid Carrier (NLC) containing active ingredient Coenzyme Q10. TIn this study, NLC were made in 3 formulas with different concentrations of cetyl palmitate as solid lipids, namely F1 10%; F2 11%; F3 12% and isopropyl palmitate as liquid lipid 3%. Several aspects such as organoleptic, homogeneity, pH, spreadability, zeta potential and particle size on NLC will be measured both before and after the stability test. The stability test used in this study uses several methods including Centrifugation, Heat Shock and Freeze-Thaw. The data were analyzed using a paired t-test. In the organoleptic tests by centrifugation, heat shock, and Feeze-Thaw, the results showed that the three formulations were homogeneous, there was no phase separation, they were semi-solid, yellow in color, and odorless. The average pH value in the Feeze-Thaw stability test of F1, F2, and F3 varied between 5.08-5.31 (before) and 5.4-5.65 (after). The results showed that differences in the concentration of cetyl palmitate as a solid lipid had a significant effect on the physical stability of NLC coenzyme Q10 on particle size which showed significant differences (p <0.05), while the concentration of cetyl palmitate had no significant effect on the pH value, Spreadability and zeta potential which showed significant results (p>0.05)